Counter-regulation in affective attentional biases: evidence in the additional singleton paradigm - Wentura, Dirk; Voß, Andreas (Quarterly journal of experimental psychology, 2018)
We investigated motivational influences on affective processing biases; specifically, we were interested in whether anticipating positive vs. negative future outcomes during goal pursuit affects attentional biases towards positive or negative stimuli. Attentional valence biases were assessed with the additional singleton task, with the task-irrelevant singleton colors being either positive, negative, or neutral. The motivational relevance of colors was established in a preceding task: in a balanced design, one color acquired positive valence by indicating the chance to win money, and a different color acquired negative valence by indicating the danger to lose money. Blocks of the additional singleton task were associated with either the chance of winning money (positive outcome focus) or the danger of losing money (negative outcome focus). We found an interaction of outcome focus and singleton valence in the accuracy rates, indicating an incongruency effect: Attentional capture was stronger for positive (negative) singletons in the negative (positive) outcome focus conditions. This result further corroborates the counter-regulation hypothesis, extending previous findings on the motivational top-down regulation of affective processing to the domain of early attentional processes.
Gesehen am 21.11.2018